Between Policy Silence and Classroom Reality: Assessing Social and Emotional Learning in Public Secondary Schools in Nyamagana District, Tanzania - Mahona Joseph Paschal; Kasara Belias Ngoboka; Night Joel (Scientia Publica Media, 2026)
It was a general consensus that the function of the Education systems in the twenty-first century was not only to improve the learning achievements of students, but also to nurture their social and emotional growth. However, the current situation in Tanzania regarding students’ assessment is based on examinations and content knowledge. While Social and Emotional Learning (SEL) is widely acknowledged as having significant importance for students’ learning achievement and citizenship development, there is no knowledge regarding students’ SEL assessment in public secondary schools in Tanzania. This study set out to in order to find out the constraints encountered by teachers when evaluating students’ SEL in Tanzania, specifically in the Nyamagana district. The study was based on Social Cognitive Theory. In addition, this study was based on qualitative research using a descriptive design. Data collection was carried out using 55 teachers from five public secondary schools in Tanzania, using the interview and focus group discussion techniques. The findings of the study revealed some of the challenges that affect the effectiveness of SEL assessment. Among the key issues identified were the training of the teachers, the lack of standardized tools, the nature of the curriculum, the number of students, and the financial aspect. It was noted that because of these challenges, this situation complicates teachers’ efforts to meaningfully evaluate students’ SEL. Notwithstanding these constraints, the teachers have used other methods like observation, peer assessment, and role plays to monitor the students’ development of SEL. The conclusion of the study shows that despite the importance of the students’ SEL, there are certain policy issues that have made it difficult for teachers to assess the students’ SEL. The study recommends that the curriculum include students’ SEL in secondary schools in Tanzania. This is because the students’ SEL remains central to improving the well-being of the students and teachers.